Students' Responses To Using Pictionary Games of Vocabulary Instructional Media - Miranty, Delsa; Fatmawati, Amelia Yustina; Hamer, Welliam (ELT Worldwide: Journal of English Language Teaching, 2023)
This paper presents a study that was undertaken to investigate the students' reactions towards the utilization of Pictionary games as a form of vocabulary educational media. The research was conducted among tenth-grade students at MAN 1 Lebak. The present study employed a descriptive quantitative approach as its chosen research methodology. The participants in this study consisted of students enrolled in class X at MAN 1 Lebak. A sample of 37 students was selected from the population of students in 10 MIA 2. The research data utilized in this study consisted of questionnaire responses obtained from students. These responses were collected to gather insights on the implementation of Pictionary games as a means of vocabulary instructional media. The results of the study indicate that the utilization of Pictionary games elicited a favorable response from the students in terms of enhancing their vocabulary proficiency. The use of Pictionary games was found to be effective in strengthening students' vocabulary skills and fostering an enjoyable learning experience.